The recovery of pig iron from the Zimbabwean limonite-coal composite pellet - S Maritsa; S M. Masuka; E K. Chiwandika (The Australasian Institute of Mining and Metallurgy, 2024)
The iron and steel industry is experiencing an increase in the use of iron and steel commodities within societies, decarbonisation pressures, depletion of high iron ore grades and high energy consumption. This necessitates scrap metal recycling, low-grade ore utilisation using the induction or electric arc furnace to achieve the global target of net zero CO2 emission. The available highquality scrap metal cannot sustain the steel industry but the world has unused hematite-goethite ores. It is the aim of this research that this resource be utilised using the induction furnace to sustain the steel industry in an environmentally friendly manner. Indurated pellets prepared from the hematite-goethite ore, 5 wt per cent limestone and 5 wt per cent coal addition were smelted in the induction furnace at 1350 ± 50°C with 25 mins holding time. The effects of basicity and carbon content were also investigated to optimise the smelting parameters. The results showed that the careful control of the basicity, and iron-to-carbon ratio maximised total metal recovery. The optimal basicity ratio was determined to be 1.3 and a carbon to iron ratio of 1.4 achieved a total metal recovery of 73 per cent. The metal recovery was closely related to the estimated slag melting temperature. The basicity ratio of 1.3 achieved the lowest slag melting temperature estimated to be around 1380°C based on the CaO-SiO2-Al2O3 phase diagram. The recovered metal had a comparable chemical composition and microstructure to that products from an ITmk3 furnace.